2013
DOI: 10.1007/978-3-642-40041-4_17
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy-Privacy Tradeoffs for Two-Party Differentially Private Protocols

Abstract: Abstract. Differential privacy (DP) is a well-studied notion of privacy that is generally achieved by randomizing outputs to preserve the privacy of the input records. A central problem in differential privacy is how much accuracy must be lost in order to preserve input privacy?Our work obtains general upper bounds on accuracy for differentially private two-party protocols computing any Boolean function. Our bounds are independent of the number of rounds and the communication complexity of the protocol, and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…The above dependency between ε and α is tight since a Θ(ε 2 )-correct, ε-differential private, protocol for computing XOR can be constructed (with information theoretic security) using the socalled randomized response approach shown in Warner [37]. It improves, in the (ε, α) dependency aspect, upon Goyal et al [13] who showed that, for some constant c > 0, a cε-correct ε-differentially private XOR implies oblivious transfer, and upon Goyal et al [12] who showed that cε 2 -correct εdifferentially XOR implies one-way functions.…”
Section: Application To Differentially Private Xormentioning
confidence: 95%
See 2 more Smart Citations
“…The above dependency between ε and α is tight since a Θ(ε 2 )-correct, ε-differential private, protocol for computing XOR can be constructed (with information theoretic security) using the socalled randomized response approach shown in Warner [37]. It improves, in the (ε, α) dependency aspect, upon Goyal et al [13] who showed that, for some constant c > 0, a cε-correct ε-differentially private XOR implies oblivious transfer, and upon Goyal et al [12] who showed that cε 2 -correct εdifferentially XOR implies one-way functions.…”
Section: Application To Differentially Private Xormentioning
confidence: 95%
“…A natural question is what assumptions are needed for such (symmetric) differentially private computation achieving certain level of accuracy. A sequence of work showed that for certain tasks, achieving high accuracy requires one-way functions [3,4,30,12]; some cannot even be instantiated in the random oracle model [16]; and some cannot be black-box reduced to key agreement [27]. See Section 1.4 for more details on these results.…”
Section: Application To Differentially Private Xormentioning
confidence: 99%
See 1 more Smart Citation
“…Considering multiplayer circumstance, multiparty differential privacy protocol can get the trade-off. Goyal et al [16] obtained general upper bounds on accuracy of two parties differential privacy protocol of computing any Boolean function. The major result was a new general geometric technique for obtaining non-trivial accuracy bounds for any Boolean functionality.…”
Section: Related Workmentioning
confidence: 99%
“…Multiparty differential privacy protocol can reach the trade-off. Goyal et al [16] obtained general upper bounds on accuracy of two parties' differential privacy protocol of computing any Boolean function. Kasiviswanathan et al [17] proposed local differential privacy that could also reach the trade-off by using random response mechanism.…”
Section: Introductionmentioning
confidence: 99%